Iron deficiency affects oxygen transport and activates HIF1 signaling pathway to regulate phenotypic transformation of VSMC in aortic dissection - Yuanyang Chen; Xu Li; Zhiwei Wang; Shun Yuan; Xiaoyan Shen; Xiaoping Xie; Kai Xing; Qingyi Zhu (BMC, 2024)
Abstract Background Aortic dissection (AD) is a macrovascular disease which is pathologically characterized by aortic media degeneration.This experiment aims to explore how iron deficiency (ID) affects the function of vascular smooth muscle cell (VSMC) and participates in the occurrence and development of AD by regulating gene expression. Methods The relationship between iron and AD was proved by Western-blot (WB) and immunostaining experiments in human and animals. Transcriptomic sequencing explored the transcription factors that were altered downstream. WB, flow cytometry and immunofluorescence were used to demonstrate whether ID affected HIF1 expression through oxygen transport. HIF1 signaling pathway and phenotypic transformation indexes were detected in cell experiments. The use of the specific HIF1 inhibitor PX478 further demonstrated that ID worked by regulating HIF1. Results The survival period of ID mice was significantly shortened and the pathological staining results were the worst. Transcriptomic sequencing indicated that HIF1 was closely related to ID and the experimental results indicated that ID might regulate HIF1 expression by affecting oxygen balance. HIF1 activation regulates the phenotypic transformation of VSMC and participates in the occurrence and development of AD in vivo and in vitro.PX478, the inhibition of HIF1, can improve ID-induced AD exacerbation.